2019
DOI: 10.21608/ejnf.2019.76354
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Acacia Saligna Leaf Meal as a Non-Traditional Feedstuff by Local Growing Hens Under Desert Conditions

Abstract: his experiment was carried out to evaluate the effect of using Acacia saligna leaf meal (ASLM) as a non-traditional feedstuff in Mamourah growing hens diets under desert conditions on the performance and economical efficiency of feed. One hundred eighty Mamourah growing hens 10 weeks of age were used in an experiment until 18 weeks of age. The experimental hens were randomly distributed into four equal groups, each group has 45 hens divided into three replicates with 15 hens each. The first group was received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…AKLM inclusion levels did not affect FI, FCR, GR, and LW of both male and female broilers during the last 3 weeks of the trial period. Similar observations were made by Lerdsuwan and Nalinanon (2017) and El-Galil et al (2019).…”
Section: Discussionsupporting
confidence: 90%
“…AKLM inclusion levels did not affect FI, FCR, GR, and LW of both male and female broilers during the last 3 weeks of the trial period. Similar observations were made by Lerdsuwan and Nalinanon (2017) and El-Galil et al (2019).…”
Section: Discussionsupporting
confidence: 90%
“…In another study, inclusion of 10% A. nilotica seed meal significantly improved weight gain and FCR with lowest feed cost per unit weight gain in broilers [ 25 ]. A. nilotica leaf meal supplementation also increase the weight gain and economic efficiency with suitable FCR in broilers [ 26 ]. Improved growth performance and FCR during this experiment and previous studies [ 13 15 ] might be due to presence of bioactive compounds in extract which stimulate the production of digestive enzymes [ 15 ] and improved the nutrients’ digestibility [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Fuentes et al (2012), Acacia schaffneri seed meal can effectively be used in the backyard production system to partially replace expensive protein and energy feed sources in poultry diets. Abd El-Galil et al (2018) also found that Acacia saligna leaf meal can be utilised in chicken diets without any negative effects on their performance and further recommended its use. However, there is limited information on the use of Acacia meals as a protein source in the diets of other poultry species such as indigenous chickens, ducks, turkeys, ostriches, and guinea fowls.…”
Section: Acacia Meals As a Protein Feed Source In Poultry Dietsmentioning
confidence: 97%
“…According to Moyo et al (2012) tannins found in leguminous trees are regarded as one natural antioxidant substance. (Ngwa et al, 2002;Mokoboki et al, 2005;Al-soqeer, 2008;Mapiye et al, 2011;Nsahlai et al, 2011;Fuentes et al, 2012;Mbongeni, 2013;Ng'ambu et al, 2013;Zia-Ul-Haq et al, 2013;Brown et al, 2016;Ncube et al, 2017b;Mthethwa, 2018;Gudiso et al, 2019;Abd El-Galil et al, 2018;Gebremeskel et al, 2019;Aruwayo et al, 2020;Otemuyiwa et al, 2020). Sources: (Mapiye et al, 2011;Fuentes et al, 2012;Mbongeni, 2013;Ncube et al, 2017b;Mthethwa, 2018;Abd El-Galil et al, 2018).…”
Section: Nutritional Value and Chemical Composition Of Acacia Speciesmentioning
confidence: 99%
See 1 more Smart Citation